(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper we will discuss Outsourcing is the commissioning of a third party (or a number of third parties) to manage a client organization.s IT assets, people and/ or activities to required results. Business process outsourcing (BPO) is a more comprehensive definition of the current situation within the outsourcing domain. BPO has become increasingly interesting as more and more business processes are commoditized and thus easier to be hosted by an external party. Cloud Computing has all the attributes and potential to support a global BPO environment. These attribute are: virtualization, service oriented architecture (SOA), utility based pricing and grid computing. Cloud Computing involves the movement of IT services . application, infrastructure and platform . onto the Internet and deployment models. Because of the high availability, high bandwidth and the increased use of the Internet it has become easier to access a variety of services, traditionally originating from within a company.s data center.